Fortis-lenis distinction of fricatives and plosives in Welsh – Phonetically distinctive factors - Baran, Michał (LingBaW. Linguistics Beyond and Within, 2020)
This paper continues a research project aimed at proving that the fortis-lenis distinction is more appropriate for studying the Welsh language than the voiced-voiceless divide. Previous analyses of articulatory timing revealed potentially distinctive features characteristic for Welsh plosives and fricatives. Even though the phonological features such as [spread glottis] or [voice] may be used both for distinguishing between the series of plosives and fricatives, the phonetic features responsible for the distinction are likely to differ due to the different phonetic nature of the manner of articulation and the position of fricatives and plosives (Honeybone 2005: 333–334). The aim of this paper is, therefore, to draw general conclusions from analysing the two sets of factors and find some universal features or characteristics of fortis and lenis obstruents in Welsh. Based on the previous studies, the importance of aspiration and voicing length are analysed in Welsh plosives. For fricatives, friction and voicing length are studied as potentially contrastive. The main hypotheses are that (i) phonetic voicing is not decisive in distinguishing between the two series of sounds in all places of articulation and (ii) other aspects of articulatory timing such as friction, aspiration length and hold phase duration appear to be more important in the fortis-lenis distinction and form a general pattern where the fortis sounds are generally longer than their lenis counterparts.